2018
DOI: 10.1016/j.nicl.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The verbal nature of worry in generalized anxiety: Insights from the brain

Abstract: BackgroundThe Cognitive Avoidance Theory of Worry argues that worry is a cognitive strategy adopted to control the physiological arousal associated with anxiety. According to this theory, pathological worry, as in Generalized Anxiety Disorder (GAD), is verbal in nature, negative and abstract, rather than concrete. Neuroimaging studies link the expression of worry to characteristic modes of brain functional connectivity, especially in relation to the amygdala. However, the distinctive features of worry (verbal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
15
0
1
Order By: Relevance
“…generalised anxiety disorder) and healthy participants. (Makovac et al, 2018;Sanders, Wang, Schooler, & Smallwood, 2017; Amsterdam Resting state questionnaire (Diaz et al, 2013) 50-items from which 5 factors can be extracted: Discontinuity of Mind, Theory of Mind, Self, Planning, Sleepiness, Comfort, and Somatic Awareness Assess thoughts and feelings experienced during rest. Sensitive to brain disorder.…”
Section: Resultsmentioning
confidence: 99%
“…generalised anxiety disorder) and healthy participants. (Makovac et al, 2018;Sanders, Wang, Schooler, & Smallwood, 2017; Amsterdam Resting state questionnaire (Diaz et al, 2013) 50-items from which 5 factors can be extracted: Discontinuity of Mind, Theory of Mind, Self, Planning, Sleepiness, Comfort, and Somatic Awareness Assess thoughts and feelings experienced during rest. Sensitive to brain disorder.…”
Section: Resultsmentioning
confidence: 99%
“…For example, other studies have reported a crucial role of the communication between amygdala and temporal pole in GAD (Li et al, 2016). Similarly, recent data have pointed to an involvement of the communication between amygdala and temporal areas in the mediation of the negative affectivity that accompanies worry in GAD (Makovac et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Extending this work to clinical conditions, especially those which are partly identifiable through their patterns of cognition, will be important. For example, studies have found that patterns of repetitive verbal thoughts can be a characteristic of anxiety [90]. Moving forward, it will be important to develop better self-report measures, more generalisable populations and to use alternative techniques for mapping neural activity to completely understand the neural correlates of different aspects of ongoing thought.…”
Section: Limitationsmentioning
confidence: 99%